2010
DOI: 10.1002/jhm.791
|View full text |Cite
|
Sign up to set email alerts
|

Advancing geriatrics education: An efficient faculty development program for academic hospitalists increases geriatric teaching

Abstract: BACKGROUND:Hospitalists care for an increasing number of older patients. As teachers, they are uniquely positioned to teach geriatric skills to residents. Faculty development programs focused on geriatrics teaching skills are often expensive and time‐intensive, and may not enhance trainee learning.OBJECTIVES:To evaluate a train‐the‐trainer (TTT) model designed to equip hospitalists with knowledge and skills to teach geriatric topics to residents in a time‐constrained, resource‐limited environment.DESIGN:Cross‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Wider implications of this study suggest that an interprofessional FDP in geriatrics may serve to increase confidence and interest in working with older adults, while also motivating changes in interprofessional practice (Berkman et al, 2000;Mazotti et al, 2010;Warshaw et al, 2007;Williams et al, 2008). The Partnership for Health in Aging competencies combined with Bandura's self-efficacy metric (2006) proved to be an effective assessment tool for measuring changes in perceived self-efficacy following the VGEC's interprofessional FDP in geriatrics.…”
Section: Concluding Commentsmentioning
confidence: 90%
See 1 more Smart Citation
“…Wider implications of this study suggest that an interprofessional FDP in geriatrics may serve to increase confidence and interest in working with older adults, while also motivating changes in interprofessional practice (Berkman et al, 2000;Mazotti et al, 2010;Warshaw et al, 2007;Williams et al, 2008). The Partnership for Health in Aging competencies combined with Bandura's self-efficacy metric (2006) proved to be an effective assessment tool for measuring changes in perceived self-efficacy following the VGEC's interprofessional FDP in geriatrics.…”
Section: Concluding Commentsmentioning
confidence: 90%
“…Key findings from the study indicated that participants reported improvements in teaching behaviour, greater educational involvement, and expanded collegial networks. Other faculty development programmes have also been successful in advancing geriatrics knowledge and enhancing teaching practice for academic hospitalists through the utilisation of a train-the-trainer model (Mazotti et al, 2010).…”
Section: Faculty Development Programmesmentioning
confidence: 99%
“…Mazotti et al 1 describe a train-the-trainer (TTT) program for hospitalists that enables hospitalists to teach geriatric medicine to house staff. We agree that it is important to ensure geriatric medicine proficiency for all hospitalists.…”
mentioning
confidence: 99%
“…Few of these addressed pedagogical or andragogical skills such as teaching and curriculum design. More‐recent geriatrics‐focused resident and faculty development programs have also continued the trend of emphasizing the teaching of geriatrics content …”
mentioning
confidence: 99%
“…More-recent geriatrics-focused resident and faculty development programs have also continued the trend of emphasizing the teaching of geriatrics content. [9][10][11] In light of the growing need to advance geriatrics care, educators at Duke University offered a program to train geriatrician and nongeriatrician faculty to design, implement, and evaluate geriatrics education curricula. This article describes the program and the results of a mixedmethod evaluation ascertaining the program's effect on participants and their home institutions.…”
mentioning
confidence: 99%